2020
DOI: 10.1001/jamacardio.2020.0239
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Outcomes in Patients With Severely Reduced Left Ventricular Ejection Fraction Undergoing Percutaneous Coronary Intervention vs Coronary Artery Bypass Grafting

Abstract: IMPORTANCE Data are lacking on the outcomes of patients with severely reduced left ventricular ejection fraction (LVEF) who undergo revascularization by percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG).OBJECTIVE To compare the long-term outcomes in patients undergoing revascularization by PCI or CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 41 publications
(62 reference statements)
3
102
0
1
Order By: Relevance
“…Other comorbidities were identified using Discharge Abstract Database, Same Day Surgery and Ontario Health Insurance Plan databases based on International Classification of Diseases 10th Revision codes within 5 years of HF diagnosis, using previously described methods. [17][18][19][20][21][22][23][24][25][26][27][28][29] Frailty was identified using the Johns Hopkins Adjusted Clinical Groups frailtydefining diagnoses indicator, which is an instrument designed and validated for research of frailty-related outcomes and resource utilisation using administrative data. 25 28 30-34 Statistical analysis Analyses were stratified by sex.…”
Section: Covariatesmentioning
confidence: 99%
“…Other comorbidities were identified using Discharge Abstract Database, Same Day Surgery and Ontario Health Insurance Plan databases based on International Classification of Diseases 10th Revision codes within 5 years of HF diagnosis, using previously described methods. [17][18][19][20][21][22][23][24][25][26][27][28][29] Frailty was identified using the Johns Hopkins Adjusted Clinical Groups frailtydefining diagnoses indicator, which is an instrument designed and validated for research of frailty-related outcomes and resource utilisation using administrative data. 25 28 30-34 Statistical analysis Analyses were stratified by sex.…”
Section: Covariatesmentioning
confidence: 99%
“…Several studies have clarified that CABG improves the clinical outcome of patients with reduced LVEF compared with PCI. 9,10,13,19 The meta-analysis by Wolff et al also reported Figure 4 The results of propensity score-matched study subgroup analysis. CABG, coronary artery bypass grafting; CI, confidence interval; CVD, cardiovascular disease; HR, hazard ratio; MI, myocardial infarction; PCI, percutaneous coronary intervention; RR, repeat revascularization.…”
Section: Discussionmentioning
confidence: 95%
“…published their work in 2017, many important studies were published; for example, Sun et al . published the largest propensity score‐matched cohort study to date 9 . This study reported that CABG was associated with a higher stroke risk than that observed with PCI for patients with severely reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic decisions are challenging for patients with advanced cardiovascular disease, because there is a paucity of evidence to support patient-centered outcomes in this group. 1,2 Traditional cardiovascular trials have sometimes been termed tombstone trials 3 because of their focus on major adverse cardiac events and death. However, a prior survey 2 of cardiovascular patients found that important outcomes identified by patients were very different from those used in traditional trials.…”
Section: Introductionmentioning
confidence: 99%